Chronic lateral epiphyseal separation of the proximal tibia causes late-onset tibia vara. Issue 1 (January 2018) - Hasegawa, Sachi; Kitoh, Hiroshi; Matsushita, Masaki; Mishima, Kenichi; Kadono, Izumi; Sugiura, Hiroshi; Kitamura, Akiko; Ishiguro, Naoki
Abstract : An adolescent obese boy showed late-onset unilateral tibia vara associated with physeal separation (slipped epiphysis) of the lateral proximal tibia and physeal widening of the lateral distal femur. These affected physes showed normal signal intensities by MRI. He was treated with lateral hemiepiphysiodesis of the left proximal tibia and the distal femur using two parallel eight-Plates, and varus deformity rapidly improved postoperatively without recurrence. This is the first case of late-onset tibia vara caused by lateral physeal separation of the proximal tibia. Normal growth of the medial physes around the knee would contribute toward significant correction after surgery.